2022
DOI: 10.3389/fpubh.2022.858482
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationships Between Problematic Social Media Use, Problematic Gaming, and Psychological Distress Among University Students: A 9-Month Longitudinal Study

Abstract: BackgroundThe causal relationships between two specific types of problematic use in internet-related activities [i.e., problematic social media use (PSMU) and problematic gaming (PG)] and psychological distress remain controversial. The present study investigated the temporal relationships between PSMU, PG, and psychological distress (i.e., anxiety, depression) in university students.MethodsHong Kong and Taiwan university students [N = 645; nmale = 266; mean = 20.95 years (SD = 5.63)] were recruited for a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 88 publications
3
17
1
Order By: Relevance
“…Concerning hypotheses tested in the cross-lagged panel model, most schools around the world adopted mandatory online teaching to maintain uninterrupted learning ( 1 , 2 , 5 , 79 ) which exposed schoolteachers to high levels of stress and may have induced inappropriate coping methods among some individuals (e.g., PIU). The findings here lend support to the I-PACE model ( 39 , 40 ) and the bidirectional lens adopted in prior studies ( 18 , 19 , 45 ). For example, prior studies have reported increased PIU among normal adults during home restriction ( 80 82 ) and the COVID-19 literature also shows that for individuals who needed to work from home, PIU was significantly correlated with psychological distress during this period ( 83 , 84 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Concerning hypotheses tested in the cross-lagged panel model, most schools around the world adopted mandatory online teaching to maintain uninterrupted learning ( 1 , 2 , 5 , 79 ) which exposed schoolteachers to high levels of stress and may have induced inappropriate coping methods among some individuals (e.g., PIU). The findings here lend support to the I-PACE model ( 39 , 40 ) and the bidirectional lens adopted in prior studies ( 18 , 19 , 45 ). For example, prior studies have reported increased PIU among normal adults during home restriction ( 80 82 ) and the COVID-19 literature also shows that for individuals who needed to work from home, PIU was significantly correlated with psychological distress during this period ( 83 , 84 ).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, in addition to the influence of psychological distress on individuals' PIU, PIU might also inversely increase psychological distress. This bi-directional association has been confirmed in recent studies ( 19 , 45 ). As addictive behaviors develop, PIU may inversely enhance an individual's negative emotions as a result of their inability to adapt to their surroundings.…”
Section: Conceptual Frameworksupporting
confidence: 79%
See 1 more Smart Citation
“…Recently, there is an increasing number of longitudinal studies on problematic social media use, some of them during COVID-19 pandemic with some conflicting results. A reciprocal relationship was reported between the level of problematic SNS use and anxiety over 9 months among Hong Kong and Taiwanese students ( 89 ). Increased insomnia and problematic SNS use was reported after 3 month follow-up among Iranian adolescents ( 90 ).…”
Section: Emotional and Social Factors Associated With Problematic Sns...mentioning
confidence: 99%
“…Therefore, in this situation, social connections among esports participants could be worse rather than being consolidated. From the perspective of psychological wellbeing, if esports is not applied properly, it can be the subjects of addiction and hence have a negative impact on a person's mental health (31)(32)(33)(34)(35).…”
Section: Esports and Social Connectednessmentioning
confidence: 99%